Gamification in the field of human resource, a creative solution for recruitment - Kovács, Tamás; Várallyai, László (International Journal of Engineering and Management Sciences, 2018)
With the introduction of latest tools and the expansion of technological solutions, the usage of smartphones ,with instant internet connection of course, has become an essential part of the net generation, also known as generation Z. At the same time, the role of IoT devices has also become part of our daily lives, completing and sometimes making it easier. This is due to the fact that the tools become more and more cheaper as time passes and parents and young people no longer consider these a technical innovations, but as a necessity. These generations; Y, Z and Alpha appear simultaneously on today’s job market, which poses a serious challenge to future HR leaders and recruiters. Because of the generational gap between them, both motivational and demanding, novel solutions are becoming increasingly appreciated in this area as well. The purpose of this study is to demonstrate the potential of gamification and to highlight the its major areas, as well as to draw the attention to "good practices" in creative recruiting through better known examples. In addition, I also tried to point out the effect on the relationship between motivation and flow-experience. The gamification method is becoming more and more popular in our country, as it plays an increasingly important role in business and education as well. In recent years, with the use of serious games, there have been several examples of HR recruitment and selection, which clearly strives to reach out to younger generations.